Réponses

Meilleure réponse !
  • Omnes
  • Modérateur confirmé
2014-05-05T00:07:18+02:00
Salut,

(x-2)(5-x) ≥ 0
x - 2 ≥0
x ≥ 2

5-x ≥0
-x≥-5
x ≤-5

S = [-inf; -5] U [2;+inf[


(1-3x)(4x+3) < 0
1 - 3x < 0
1 < 3x
x > 1/3

4x + 3 < 0
4x < -3
x < -3/4

S = ]-inf; -3/4[ U ]1/3; +inf[


3x(4-x) ≥0
3x ≥ 0
x ≥ 0

4-x ≥0
-x ≥ -4
x ≤ 4

S = [0;4]

(2x-1)(2x+1) < 0
2x - 1 < 0
2x < 1
x < 1/2

2x + 1 < 0
2x < -1
x < -1/2

S = ]-inf; 1/2[


x(3-x)(2x+1) > 0
x > 0
3-x > 0
-x > -3
x < 3

2x + 1> 0
2x > -1
x > -1/2

S = ]-1/2;3[


(2x-1)(4-5x)(x+2) ≤ 0
2x - 1 ≤ 0
2x ≤ 1
x ≤ 1/2

4 -5x ≤ 0
-5x ≤ -4
x ≥ 4/5

x + 2 ≤ 0
x ≤ -2

S = ]-inf; 1/2] U [4/5; +inf[

Bonne soirée !
mec sérieusement je te remercie pour ton aide inoubliable. .. merci beau